Gambaran Tingkat Kejenuhan (Burnout) dan Motivasi Sembuh Klien Rehabilitasi Narkoba di Plato Foundation - Fahrizal Amin Nurfaizi; Savira Auliya Abdullah; Atik Qurrota A’ Yunin Al Isyrofi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Drug abusers experience several difficulties while undergoing rehabilitation programs, one of which is a lack of motivation to recover. Lack of self-motivation causes several problems for drug abusers in rehabilitation, one of which is boredom which can hinder the recovery process. Motivation and boredom of drug rehabilitation patients need to be considered because they greatly affect the success of the rehabilitation process. The purpose of this study was to determine the level of saturation and recovery motivation of drug rehabilitation clients at Plato Foundation. This research uses a descriptive quantitative study with a cross-sectional approach method and data collection is done by distributing questionnaires to 15 respondents with a sampling method, namely the total population. Based on the results of the study, it shows that 60% of respondents do not experience saturation and 40% experience feelings of saturation and as many as 80% of respondents have high recovery motivation and 20% of respondents have low recovery motivation. The role of activities and activities greatly affects the motivation and burnout of drug abusers while undergoing a rehabilitation program.